Transient vibration analysis of unit-plant structure for hydropower station in sudden load increasing process. (1st April 2019) - Zhang, Leike; Wu, Qianqian; Ma, Zhenyue; Wang, Xueni
Highlights: A mathematic model of hydraulic excitation induced by draft tube vortex is proposed. A model for studying transient vibration of hydroelectric system is established. Transient vibration behavior of unit-plant structure for sudden load-up is analyzed. Reasons for large transient oscillation of unit-plant structure are studied. Difference between stable and instable vibration of system is discussed in detail. Abstract: The vibration problem of hydraulic generating unit and plant structures in hydropower station influenced mainly by pressure fluctuation of draft tube and other factors during the transient process is dramatic, whereas the relevant theoretical research is seriously lagged behind the actual engineering practice. Aiming at this present condition, firstly, a mathematical expression of hydraulic excitation induced by draft tube vortex under different load conditions is proposed from the perspective of theoretical analysis. Then, based on the hydraulic-mechanical-electrical-structural model of hydroelectric generation system established previously, the sudden load increasing transition process is incorporated into the investigation system of unit-plant structure vibration, and the corresponding dynamic characteristics under this non-stable operation condition are studied. The calculation results show that, compared with steady working condition, the operation stability of unit shaft system is decreased and the matching vibration amplitude is obviously increased during the transient process. Meanwhile, in contract to the unit shaft system, the oscillation phenomenon of generator floor in hydropower plant is more significant. In particular, the vertical direction vibration is extremely prominent that the displacement amplification can even reach several times of that when the system is operated stably. The research in this paper can not only reflect the vibration behavior of unit-plant structure in sudden load-up process to some extent, but also provide reasonable and reliable analysis model and method for dynamic response exploration, stability investigation, as well as fault diagnosis for the hydraulic generating unit and hydropower plant structures.